2021
DOI: 10.1108/wje-09-2020-0459
|View full text |Cite
|
Sign up to set email alerts
|

Advance control strategies using image processing, UAV and AI in agriculture: a review

Abstract: Purpose The purpose of this paper is to provide an overview of smart agriculture systems and monitor and identify the technologies which can be used for deriving traditional agriculture system to modern agriculture system. It also provides the reader a broad area to work for the advancement in the field of agriculture and also explains the use of advanced technologies such as spectral imaging, robotics and artificial intelligence (AI) in the field of agriculture. Design/methodology/approach Smart uses of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The cluster ‘IMAGE PROCESSING’ ( Figure 4 f) presents strong linkages with agricultural management tools (e.g., ‘MACHINE VISION’ and ‘COMPUTER VISION’) that provide data for the farmer’s decision-making. Previous literature reviews explored advanced control strategies and image processing techniques in Digital Agriculture (see Ngugi et al (2021) [ 125 ], Syeda et al (2021) [ 126 ], and Sohail et al (2020) [ 127 ]). Zhao et al [ 128 ] used machine vision to exploit color images to detect immature green citrus.…”
Section: Resultsmentioning
confidence: 99%
“…The cluster ‘IMAGE PROCESSING’ ( Figure 4 f) presents strong linkages with agricultural management tools (e.g., ‘MACHINE VISION’ and ‘COMPUTER VISION’) that provide data for the farmer’s decision-making. Previous literature reviews explored advanced control strategies and image processing techniques in Digital Agriculture (see Ngugi et al (2021) [ 125 ], Syeda et al (2021) [ 126 ], and Sohail et al (2020) [ 127 ]). Zhao et al [ 128 ] used machine vision to exploit color images to detect immature green citrus.…”
Section: Resultsmentioning
confidence: 99%
“…This model backbone affected the accuracy, but the depth of the backbone increased, and the accuracy of the segmentation did not increase. The outcomes showed that the majority of segmentation models used either ResNet34 or ResNet50 as their suitable backbone (Syeda et al 2021). The author utilized UAV images to develop an enhanced YOLOv5-based early wildfire smoke detection system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the utilization of image processing has expanded its reach into various sectors including education [1], healthcare [2], agriculture [3], unmanned aerial vehicles (UAVs) [4], and numerous other domains. Advancements in technology have helped the agriculture industry apply a profound transformation to prosper farming and eliminate challenges and issues [5]. Employing UAVs in agriculture has made a revolution because of providing real-time data for farmers to take action on time with more productivity (e.g., [6], [7]).…”
Section: Introductionmentioning
confidence: 99%